Evaluating the relationship between communication management practices and project outcomes: a case study of Eswatini (Swaziland) construction industry (Construction Economics and Building, 2019)
Communication management is viewed as an imperative factor associated with performance improvement in construction projects. In Eswatini, it is established that projects experience poor project delivery associated with poor communication management practices. This study seeks to elucidate communication management practices informed by local culture and relate it to project outcome. A questionnaire survey of practitioners registered with Eswatini construction industry council was adopted for the study. Data was collected from 66 respondents. Principal axis factoring established nine practices namely; information technology, communication technology, communication skills and competence, communication management plan, teamwork, clear channels within organisation’s structure, project brief requirement management, project brief risk requirement management and context of environment as being key factors to project positive outcome. Spearman’s rho established that a relationship exists between project outcome and three practices namely; information technology, communication management plan and clear channels within organisation’s structure. The findings present key empirical evidence of the communication management practices that relate to project outcome in Eswatini. The study contributes on communication management practices in Eswatini and its relation on project outcome. Limitation of the study conclude that results and analysis cannot be generalised. However, the findings from the research provides opportunities for extensive further research recommendations to assess, refine and understand the effect of the variable’s communication management practice to project outcome.